Antibodies to Oligodendrocyte Glycoprotein in Children with ADEM - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Antibodies to native myelin oligodendrocyte glycoprotein (nMOG) in 47 children during a first episode of CNS demyelination (acute disseminated encephalomyelitis [ADEM] in 19, and a clinical isolated syndrome [CIS] in 28) were investigated by a cell-based bioassay in a study at Children's Hospital at Westmead, Sydney, Australia, and at the University of Munich, Germany.